2008
DOI: 10.3923/pjbs.2008.2433.2437
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bovine leukemia virus p24 Protein in Bacterial Cell

Abstract: Bovine leukemia virus (BLV) is a member of the family Retroviridae, genus Deltaretrovirus that has three important gene including gag, pol and env. This virus causes B-cell lymphocytosis and lymphosarcoma in cows. In the first step PCR product of gag gene of BLV isolated in different regions of Iran and BLV-FLK strain were cloned in to a pTZ57R/T vector, then insert were digested by BglII and XhoI restriction enzymes and cloned in to pET-28(a) as an expression vector. For the expression of p24 protein, the pET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The serological tests used for diagnosis of bovine leukemia include the Agar Gel Immuno Diffusion (AGID) and the Enzyme-Linked Immuno Sorbent Assay (ELISA) (Momtaz et al 2008, OIE 2012. Both tests are less sensitive when compared to polymerase chain reaction (PCR) described by several researchers (OIE 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The serological tests used for diagnosis of bovine leukemia include the Agar Gel Immuno Diffusion (AGID) and the Enzyme-Linked Immuno Sorbent Assay (ELISA) (Momtaz et al 2008, OIE 2012. Both tests are less sensitive when compared to polymerase chain reaction (PCR) described by several researchers (OIE 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of proteins from different viruses, such as bovine immunodeficiency virus [23] and bovine respiratory syncytial virus [24], has been already described. In the last decade, BLV gag proteins p24 have been expressed in heterologous expression systems such as Escherichia coli [25][26][27][28] or Saccharomyces cerevisiae [29]. In a direct comparison study for recombinant protein production in the E. coli, Pichia pastoris, Saccharomyces cerevisiae and Spodoptera frugiperda systems, Christopher et al [30] reported that baculovirus-mediated expression in Sf21 cells is the most efficient system capable of producing large amounts of recombinant protein.…”
Section: Discussionmentioning
confidence: 99%